Node.js 6.x blueprints : create stunning web applications and restful APIs from start to finish with Express, Loopback, MongoDB, and MySQL using this definitive guide - Monteiro, Fernando (Community experience distilled., 2016)
Create stunning web applications and Restful APIs from start to finish with Express, Loopback, MongoDB, and MySQL using this definitive guide About This Book Create stunning applications with Node.js from scratch, no matter the goal Discover a wide variety of applications you can effectively integrate third-party libraries and other front-end frameworks with Node.js Leverage all the new features introduced in Node.js 6.X Who This Book Is For This book caters to developers who are looking to build projects right from a simple website to more complex one such as a blog, chat application, a photography site, and a lot more. A Basic knowledge of JavaScript and Node.js would be extremely beneficial. What You Will Learn Explore MVC design pattern in Node.js Build solid architectures by following test-driven development Look beyond web applications and create your own desktop app with Node.js Develop single page applications using Node.js with the RESTful APIs, MongoDB, and ORM Master the Express framework and build a complete application with a real database Create a real-time and fully functional online chat application with Socket.IO In Detail Node.js is the most popular framework to create server-side applications today. Be it web, desktop, or mobile, Node.js comes to your rescue to create stunning real-time applications. Node.js 6.x Blueprints will teach you to build these types of projects in an easy-to-understand manner. The key to any Node.js project is a strong foundation on the concepts that will be a part of every project. The book will first teach you the MVC design pattern while developing a Twitter-like application using Express.js. In the next chapters, you will learn to create a website and applications such as streaming, photography, and a store locator using MongoDB, MySQL, and Firebase. Once you're warmed up, we'll move on to more complex projects such as a consumer feedback app, a real-time chat app, and a blog using Node.js with frameworks such as loopback.io and socket.io. Finally, we'll explore front-end build processes, Docker, and continuous delivery. By the end of book, you will be comfortable working with Node.js applications and will know the best tools and frameworks to build highly scalable desktop and cloud applications. Style and approach This is an easy-to-follow guide full of practical examples. This book takes a project-based approach and each chapter contains step-by-step instructions to create stunning application...